PERSEPSI PENGUNJUNG TENTANG FASILITAS OBJEK WISATA GUNUANG PADANG DI KOTA PADANG - Azima, Fauzan; Silfeni, Silfeni; Suyuthie, Hijriyantomi (Journal of Home Economics and Tourism, 2017)
The purpose of this research is to know the Perception of Visitors AboutFacilities at Gunuang Padang. The type of research is descriptive quantitative. Thevisitor population in tourist attraction is 1.493 people. Selection of this researchsample using purposive sampling technique counted 94 people. Data collectionusing questionnaires based on Likert Scale that has been tested for its validity andreliability. The result of Perception of Visitors About Facilities at GunuangPadang is categorized well with the average value of 90.62 which is in the range86.66 - 103.99. While based on each indicator are: (1) form of tourism facilitypertained in good category with average value equal to 20,88 is in range of score20,16 - 24,49, (2) function of tourism facility pertained in good category with anaverage score of 28.55 is in the range of the score 23.74 - 30.25, (3) the locationof tourism facilities belonging to the good category with an average value of20.78 is in the range of the score 20.16 - 24, 49, (4) the quality of tourismfacilities is categorized as good category with an average value of 20.52 is in therange of 20.16 - 24.49 score.